Factors associated with adherence to colonoscopy among individuals who were positive in the preliminary screening for colorectal neoplasms. (20th April 2022) - Li, Ji‐Bin; Ke, Keng‐Jian; Zhang, Wei‐Li; Wang, Ling‐Yan; Wu, Yan‐Ping; Weng, Fan; Tian, Huan; Qiu, Zhi‐Yu; Li, Yin; Lin, Shi‐Yong; Ye, Mei‐Xian; Ou, Qing‐Jian; et al.
Abstract: Objectives: This study aimed to investigate the potential factors associated with adherence to colonoscopy among participants who were preliminarily screened positive in a community‐based colorectal cancer screening program in China. Methods: This study analyzed data from 1219 out of 6971 community residents who were identified as positive cases by the well‐validated high‐risk factor questionnaire (HRFQ) or fecal immunochemical test (FIT) in the preliminary screening stage for colorectal neoplasms. Patients showing adherence to colonoscopy were defined as those who received positive results in a preliminary screening for colorectal neoplasms and later received a colonoscopy examination as required. The associations of social‐demographic factors, lifestyle behaviors, history of diabetes, body mass index (BMI), and risk factors in the HRFQ with adherence to colonoscopy were evaluated using logistic regression models. Results: Among 1219 participants who preliminarily screened positive, the top five risk factors reported by the participants were chronic constipation (25.9%), hematochezia (23.5%), family history of CRC in first‐degree relatives (22.1%), chronic diarrhea (21.8%), and history of polyps (16.6%). Around 14.2% of participants who preliminarily screened positive reported three or more risk factors, and the proportion was 26.2% among participants who were positive according to both HRFQ and FIT. Among all participants who were preliminarily screened positive, the multivariable results showed that those who were married (OR = 1.58, 95% CI: 1.12, 2.25, p = 0.01), had chronic diarrhea (OR = 1.34, 95% CI: 1.00, 1.78, p = 0.047), and had a positive FIT (OR = 1.60, 95% CI: 1.21, 2.10, p < 0.001 for patients who were negative according to HRFQ but positive according to FIT; OR = 2.12, 95% CI: 1.33, 2.78, p = 0.002 for patients who were positive for both HRFQ and FIT) were more likely to adhere to colonoscopy, while participants with a history of cancer (OR: 0.50, 95% CI: 0.31, 0.79, p = 0.003) were less likely to adhere to colonoscopy. The results among participants who were tested positive according to only HRFQ were similar to those among all participants who were tested positive according to HRFQ or FIT. However, among participants who were tested positive according to only FIT, we only found that those who were married (OR = 2.52, 95% CI: 1.08, 5.90, p = 0.033) had a higher odds of adhering to colonoscopy, while those with a history of diabetes (OR = 0.35, 95% CI: 0.13, 0.96, p = 0.042) were less likely to adhere to colonoscopy. Conclusion: Our findings provide evidence supporting the development of tailored interventional strategies that aim to improve adherence to colonoscopy for individuals with a high risk of colorectal neoplasms. Both barriers and facilitators associated with adherence to colonoscopy should be considered in supportive systems and health policies. However, further well‐designed prospective studies are warranted to confirm our findings. Abstract : For the participation rate of colonoscopy screening is still disappointingly low in China. We find out the factors associated with colonoscopy adherence among individuals who were positive in the preliminary screening for colorectal neoplasms.